(untitled) (Economia Aplicada, 2003)
The purpose of this paper is to analyze the political economy and evolution of exchange arrangement. The choice of the exchange rate arrangement is dependable a set of economic framework indicators The evidences show that a particular exchange rate arrangementis characterized by dynamic inconsistency, that is, it can not be the only one all the time. The results point out that the majority of countries is giving up the intermediary exchange rate regimes and moving to bipolar ones. Of course the flexible exchange rate is preferable.